TGFβ1 attenuates microglial IL1β release through inhibition of NLRP3 inflammasome priming - Kalischer, Christopher; Potru, Phani Sankar; Lehmann, Nele; Jahn, Jannik; Rupp, Nikolai Leander; Vidovic, Natascha; Russ, Tamara; Wiemann, Susanne; Spittau, Björn (Frontiers in Immunology, 2026)
IntroductionMicroglia reactivity has been described as a driver of brain tissue damage in multiple neurodegenerative pathologies. One of the key features of reactive microglia is the transcriptional upregulation of in ammatory markers, including components of the NLRP3 inflammasome such as Nlrp3, Casp1, and Il1b. The NLRP3 inflammasome is a multiprotein complex that plays an important role in several neurodegenerative diseases, being essential for cleavage and subsequent release of IL1b from activated microglia. Transforming growth factor β1 (TGFβ1) is a potent immunoregulatory cytokine with fundamental roles in microglial development, maintenance, and regulation of microglia reactivity.MethodsUsing BV2 cells, primary microglia, qPCR, and western blotting the effect of TGFβ1 on LPS-induced inflammasome priming and activation was addressed. Cx3cr1CreERT2:R26-YFP: Tgfbr2flox/flox mice were used to elucidate priming in the absence of microglial TGFβ signalling. ResultsIn the present study, we demonstrate that TGFβ1 is able to abrogate LPS-induced transcriptional upregulation of the inflammasome-associated genes Nlrp3, Casp1, and Il1b in microglia. Moreover, we provide evidence that TGFβ1 attenuates microglial IL1b release after nigericin-triggered NLRP3 inflammasome activation as a consequence of reduced priming.Finally, we demonstrate that silencing of microglial TGFβ signalling in vivo results in upregulation of Casp1, Il18, and Il1b. DiscussionTogether, our data enhance the understanding of how TGFβ1 and microglial TGFβ signaling regulate microglial reactivity, further highlighting the essential functions of TGFβ1 as a potentimmunoregulatory factor for microglia.